Produção e percepção do /R/ em coda silábica como marca do falar caipira - Santos, Romilda Ferreira (2024)
This research aims to describe and analyze the production and perception of the retroflex variant in syllabic coda as a mark of caipira speech, having as corpus the speech of informants from Ituiutaba and Uberlândia, cities located in the Triângulo Mineiro region, in the state of Minas Gerais. The motivation for this study came from the observation that different sociolinguistic research has been developed to address the variation present in Brazilian Portuguese. Regarding the state of Minas Gerais, there is extensive research in Sociolinguistics, and they have contributed significantly to the sociolinguistic design of Minas Gerais. However, all the research was still insufficient to present that state’s complexity. This gap can be noted when it comes to the caipira dialect present in the Triângulo Mineiro, which is still often identified (or stigmatized) via specific variants, such as the use of the retroflex variant of /R / in syllabic coda: ca[ɻ]ne. In this sense, it is evident that studies that contribute to describing regional speech in the Triângulo Mineiro are necessary. Considering the theoretical-methodological assumptions of Variationist Sociolinguistics (LABOV 2008 [1972]), we conducted 24 interviews with twelve informants from each city for production research. For the perception tests, we used the verbal guise test technique (AGHEYISI AND FISHMAN, 1970) and, based on stimuli with the retroflex variant and the fricative variant, we created two virtual forms and one face-to-face, which we obtained a total of 86 answers. We transcribed and coded the collected data and did the manipulation using the computer program R. The results from the linguistic production questionnaires demonstrated, in general, that the retroflex variant is the most productive in both locations. In the universe of 8508 data, we verified only 285 occurrences of other variants. Regarding the extralinguistic independent variables, the data revealed that, concerning the age group, the use of the retroflex variant was more recurrent in the three age groups. Regarding education, our p-value analysis revealed that we are facing a null hypothesis: the level of education does not (dis)favor the realization of the retroflex variant. Linguistically, we found that the retroflex variant is favored in the following contexts: labial and coronal vowels, coronal consonants, unstressed syllables, non-verbs, words with one and two syllables and coda in initial and medial syllable. As for the perception tests, data analysis revealed that residents of both locations perceive the production of retroflex /R/ in their speech and the speech of other residents of the region and attribute different valuations to the two variants present in the test: fricative and retroflex. We also found that most respondents from both locations identify the retroflex variant as a mark of caipira speaking. Finally, the data revealed that the negative valuation attributed to the retroflex variant is external to the speech communities of Ituiutaba and Uberlândia, that is, it is given by speakers of other variants. For the respondents who belong to the analyzed communities and use the retroflex variant, it marks their social place through a form of linguistic identification of which they are proud.